A study of temperature effects on car coated substrate in laser paint removal - Mohammad Khairul Azhar Abdul Razab; Mohamad Suhaimi Jaafar; Azhar Abdul Rahman (2014)
Cynosure Cynergy Pulse Nd:YAG laser was used to